In Vitro and In Vivo Metabolic Activation of Obacunone, A Bioactive and Potentially Hepatotoxic Constituent of Dictamni Cortex - Lang, Xiuzhuang; Zhang, Xiangmei; Wang, Daoquan; Zhou, Weiqing (Planta Medica, 2020)
Obacunone is one of the major bioactive constituents from Dictamni cortex, a traditional Chinese medicine widely used in China. Oral administration of obacunone or Dictamni cortex extract has been shown to cause liver injury in rats. Given that obacunone contains a furan ring, which is a structural alert, metabolic activation might be responsible for obacunone-induced liver injury. In this study, bioactivation pathways of obacunone in rat and human liver microsomes were investigated. Obacunone was first metabolized into cis-butene-1,4-dial, and then cis-butene-1,4-dial was captured by glutathione, N-acetyl-cysteine, and N-acetyl-lysine in the microsomal incubation system. A total of 13 adducts derived from the reaction of cis-butene-1,4-dial with glutathione and/or N-acetyl-lysine were detected and structurally identified by liquid chromatography coupled to high-resolution tandem mass spectrometry. The major metabolite (M7) was identified to be the cyclic mono-glutathione conjugate of cis-butene-1,4-dial, which was detected in bile and urine of obacunone-treated rats. M9 and M10, obacunone-derived glutathione-cis-butene-1,4-dial-NAL conjugates, were detected in the microsomal incubations of obacunone fortified with glutathione and N-acetyl-lysine as trapping agents. M3 and M4, pyrroline-2-one derivatives, were also detected in microsomal incubations. Further phenotyping studies indicated that ketoconazole showed a strong inhibitory effect on the production of cis-butene-1,4-dial in a concentration-dependent manner. CYP3A4 was demonstrated to be the primary enzyme responsible for the bioactivation of obacunone by using individual recombinant human CYP450 enzymes. The current study provides an overview of CYP450-dominated bioactivation of obacunone and contributes to the understanding of the role of bioactivation in obacunone-induced liver injury.
Keywords: Obacunone; cis-butene-1,4-dial; CYP3A4; Dictamni cortex; Dictamnus dasycarpus; Rutaceae; metabolic activation